The industrial anaerobe Clostridium acetobutylicum uses polyketides to regulate cellular differentiation. Issue 1 (December 2017) - Herman, Nicolaus; Kim, Seong; Li, Jeffrey; Cai, Wenlong; Koshino, Hiroyuki; Zhang, Wenjun
Abstract Polyketides are an important class of bioactive small molecules valued not only for their diverse therapeutic applications, but also for their role in controlling interesting biological phenotypes in their producing organisms. While numerous polyketides are known to be derived from aerobic organisms, only a single family of polyketides has been identified from anaerobic organisms. Here we uncover a family of polyketides native to the anaerobic bacteriumClostridium acetobutylicum, an organism well-known for its historical use as an industrial producer of the organic solvents acetone, butanol, and ethanol. Through mutational analysis and chemical complementation assays, we demonstrate that these polyketides act as chemical triggers of sporulation and granulose accumulation in this strain. This study represents a significant addition to the body of work demonstrating the existence and importance of polyketides in anaerobes, and showcases a strategy of manipulating the secondary metabolism of an organism to improve traits relevant for industrial applications. Polyketides are secondary metabolites mainly found in aerobic organisms with wide applications in medicine and agriculture. Here, the authors uncover new polyketides native to the anaerobic bacteriumClostridium acetobutylicum and show their role in triggering sporulation and granulose accumulation.